Influence of the bcg locus on natural resistance to primary infection with the facultative intracellular bacterium Francisella tularensis in mice - Kovárová, H; Hernychová, L; Hajdúch, M; Sírová, M; Macela, A (Infection and immunity, 2000)
The implication of the Bcg locus in the control of natural resistance to infection with a live vaccine strain (LVS) of the intracellular pathogen Francisella tularensis was studied. Analysis of phenotypic expression of natural resistance and susceptibility was performed using mouse strains congenic at the Bcg locus. Comparison of the kinetics of bacterial colonization of spleen showed that B10.A.Bcg(r) mice were extremely susceptible during early phases of primary sublethal infection, while their congenic C57BL/10N [Bcg(s)] counterparts could be classified as resistant to F. tularensis LVS infection according to the 2-log-lower bacterial CFU within the tissue as long as 5 days after infection. Different phenotypes of Bcg congenic mice were associated with differential expression of the cytokines tumor necrosis factor alpha, interleukin-10, and gamma interferon and production of reactive oxygen intermediates. These results strongly suggest that the Bcg locus, which is close or identical to the Nramp1 gene, controls natural resistance to infection by F. tularensis and that its effect is the opposite of that observed for other Bcg-controlled pathogens.
Keywords: přirozená imunita; Chromosome Mapping; dusitany; slezina; tularemie; reaktivní formy kyslíku; membránové proteiny; cytokiny; Nitrites; Membrane Proteins; Cation Transport Proteins; Immunity, Innate; Spleen; Carrier Proteins; Reactive Oxygen Species; kultivované buňky; Animals; ženské pohlaví; mapování chromozomů; zvířata; Tularemia; myši inbrední C57BL; myši; Mice, Inbred C57BL; Cells, Cultured; Cytokines; Mice; Female; transportní proteiny; proteiny přenášející kationty